2022
DOI: 10.1093/ofid/ofac167
|View full text |Cite
|
Sign up to set email alerts
|

Relative Effectiveness of MF59 Adjuvanted Trivalent Influenza Vaccine vs Nonadjuvanted Vaccines During the 2019–2020 Influenza Season

Abstract: Background Age-related immunosenescence may impair the immune response to vaccination in older adults. Adjuvanted influenza vaccines are designed to overcome immune senescence in older adults. This study estimated the relative vaccine effectiveness (rVE) of MF59®-adjuvanted trivalent inactivated influenza vaccine (aIIV3) versus egg-derived quadrivalent inactivated influenza vaccine (IIV4e) and high-dose trivalent inactivated influenza vaccine (HD-IIV3) in preventing influenza-related medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 38 publications
(29 reference statements)
0
17
0
6
Order By: Relevance
“…The dataset for each retrospective cohort study included only de-identified clinical data that met Protected Health Information (PHI) data requirements and were certified for Health Insurance Portability and Accountability Act (HIPAA) compliance. The studies were conducted and reported in accordance with Good Pharmacoepidemiological Practice from the Declaration of Helsinki, which is applicable to local regulations, and the Reporting of Studies Conducted using Observational Routinely Collected Health Data (RECORD) [22][23][24][25][26]28].…”
Section: Methodology Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The dataset for each retrospective cohort study included only de-identified clinical data that met Protected Health Information (PHI) data requirements and were certified for Health Insurance Portability and Accountability Act (HIPAA) compliance. The studies were conducted and reported in accordance with Good Pharmacoepidemiological Practice from the Declaration of Helsinki, which is applicable to local regulations, and the Reporting of Studies Conducted using Observational Routinely Collected Health Data (RECORD) [22][23][24][25][26]28].…”
Section: Methodology Of Individual Studiesmentioning
confidence: 99%
“…During the next season, subjects were vaccinated from 1 August 2018 through 28 February 2019 and the observation period was 1 August 2018 through 18 May 2019 [23]. In the 2019-2020 season, subjects were vaccinated from 1 August 2019 through 31 January 2020 and the observation period was 29 September 2019 through 7 March 2020-an early cut-off to avoid potential bias arising from the coronavirus disease 2019 (COVID-19) pandemic [25,26]. Overall inpatient or outpatient influenza-related medical encounters (IRMEs)-the primary outcome in all studies-were defined using the International Classification of Diseases (ICD)-9-CM and ICD-10-CM codes that correspond to the US Armed Forces Health Surveillance Center (AFHSC) Code Set B (Table S2) [29].…”
Section: Methodology Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations